Gilles Deleuze : el filósofo como educador (2011)
ABSTRACT: This paper aims to address part of the life of French philosopher Gilles Deleuze as an educator, this being a suggestive trace for the construction of Body Education. I will leave aside (just for now) his philosophical thought for emphasis to developments which traced its evolution as a teacher. Body Educational this thinker has been very suggestive, its critical nature is drawing other ways in which transit. It is impossible to deny the contributions to the education of a philosopher, but also a teacher for over 40 years, seducer of youth and adults in their classes cataloged by him as “a kind of matter in motion musical” (Parnet, 1988). Take a walk then some of his experiences as a student and a teacher and get to know a little more of his ‘exceptional pedagogy’, as we say Dosse (2009)